دور إستراتيجية تعلم الموارد البشرية في تفعيل المسؤولية الاجتماعية للمؤسسات – دراسة ميدانية لبعض المؤسسات الاقتصادية بولايتي سطيف وبرج بوعريريج – - بورغدة, حسين; مساعدية, عماد (جامعة الوادي - University of Eloued, 2017)
يعتبر المورد البشري أهم مورد في المؤسسة لذا يجب التعامل معه وفق منظور إستراتيجي لجعله أكثر استعدادا لمواجهة التغيرات الحاصلة في بيئة الأعمال، وتعتبر إستراتيجية التعلم من أهم الاستراتيجيات التي تتبعها المؤسسات لزيادة كفاءة مواردها البشرية وتحقيق أهدافها الاقتصادية والاجتماعية والبيئية ومنه تحقيق المسؤولية الاجتماعية للمؤسسات، تهدف هذه الدراسة إلى التعرف على دور إستراتيجية تعلم الموارد البشرية في المؤسسات الاقتصادية في تحقيق المسؤولية الاجتماعية للمؤسسات من خلال دراسة ميدانية قمنا بها على بعض المؤسسات الاقتصادية في ولايتي سطيف وبرج بوعريريج. The human resource most important resource in the organization so must be dealt with in accordance with the strategic perspective to make it more prepared to face the changes in the business environment changes, and is considered the learning strategy of the main strategies used by the institutions to increase the efficiency of human resources and to achieve economic, social and environmental objectives and from the achievement of corporate social responsibility, aims study was to investigate the role of human resources learning strategy in the economic enterprises in the achievement of corporate social responsibility through a field study we made some economic enterprises in the states of Setif, Bordj Bou Arreridj.
The role of Human Resources Learning Strategy in activating corporate social responsibility-study of some economic institutions in the states of Setif and Burj Bou Arreridj
مقال
Keywords: إستراتيجية التعلم، المسؤولية الاجتماعية للمؤسسات، أبعاد المسؤولية الاجتماعية للمؤسسات; Learning strategy, corporate social responsibility, the dimensions of corporate social responsibility.